Clinical correlation of foot eczema and patch test: a cross sectional study from South India - Fathima, Sharim; Muhammed, Kunnummal; Nandakumar, Gopalapillai (International Journal of Research in Dermatology, 2021)
Background: Foot eczema is caused by several exogenous or endogenous factors acting alone or in combination. Leather, rubber and adhesive components are the most common allergens. Patch test is performed to find out the allergen which helps clinician in subsequent patient management and improving the prognosis. Methods: Total 50 patients with foot eczema were evaluated and patch test was performed with Indian standard series over 18 months period in a tertiary hospital in South India. Results: Out of 50 patients 32 (64%) were females and 18 (36%) were males. Younger age group was mainly involved (second decade). An atopic back ground and seasonal exacerbation were contributory in many. Patch test was positive in 39 (78%) patients. The forefoot was predominantly involved part in 56% followed by dorsal aspect alone of the foot. Scaly plaque was the predominant morphological pattern seen in 25 (50%). Maximum number of patients (24%) showed positive reactions to potassium dichromate and the minimum (2%) to neomycin sulphate. Conclusions: Though rubber and rubber chemicals were the common sensitizers causing foot eczema worldwide, our study found potassium dichromate to be the most common sensitizer which is one the components used in leather tanning and is a constituent of cement, soaps and detergents.